Sosialisasi Penguatan Wawasan Kesiapsiagaan Bencana dalam Merespons Desa Tanggap Bencana di Desa Doyong Kabupaten Sragen - Nindi Anjani; Nuvaisha Nur Madhan; Okkydhian Vicky Astraedha; Qobitha Ocha Fishara Qoirunnisa; Safitri Setyorini (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Desa Doyong is one of the villages located in Miri District, Sragen Regency, Central Java. The natural disaster of flooding in Doyong Village occurred in 2023, with a prolonged water recession process. Besides floods, droughts and strong winds also occurred due to extreme weather. The community's unpreparedness in facing disasters resulted in social and economic impacts. Therefore, the purpose of this community service is to enhance the knowledge, abilities, and independence of the community in facing and addressing disaster issues, as well as to build community preparedness for potential future disasters. The research employs a descriptive qualitative approach, collecting primary data through in-depth interviews, observations, and focus group discussions (FGDs). Secondary data were obtained from official BPBD documents, documentation, and relevant literature. Activities included rainfall mapping, community and school disaster preparedness education, the Village Clean Week (GUBERDES) program, reforestation, and collaboration with BPBD Sragen Regency. Results indicate that effective resource mobilization and involvement of various stakeholders, can improve community disaster preparedness.